The Impact of Professionality, Credibility, and Ease of Use on Repurchase Intentions via E-Satisfaction Among Gen Z in TikTok Shop - Saputra, Dativa Robert; Sugiarto, Catur (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyse the impact of professionality, credibility, ease of use, and security on repurchase intention in TikTok Shop, mediated by customer satisfaction among Generation Z. The research employs a quantitative approach with data collection through online questionnaires distributed to 390 respondents who are active users of TikTok Shop. The findings show that professionality, credibility, ease of use, and security have a positive influence on repurchase intention, both directly and through mediation by customer satisfaction. These results provide valuable insights for TikTok Shop managers to enhance the shopping experience and encourage repurchase intention among consumers.